Efek Ganda Jus Kombinasi Nanas Madu (Bromelia comosa) dan Buah Naga (Selenicereus monacanthus) sebagai Analgesik dan Gastroprotektor pada Mencit - Maryam Jamila Arief; Gayuk Kalih Prasesti; Nur Rezky Khairun Nisaa (JURNAL FARMASI DAN MAKANAN, 2026)
The widespread use of nonsteroidal anti-inflammatory drugs is often associated with gastrointestinal adverse effects, highlighting the need for safer alternatives. This study aimed to evaluate the analgesic and gastroprotective potential of a combination of honey pineapple and dragon fruit juices in mice. Analgesic activity was assessed using the acetic acid-induced writhing test with aspirin as the positive control, while gastroprotective effects were evaluated using an aspirin and hydrochloric acid-induced gastric ulcer model with sucralfate as the reference drug. The test samples consisted of three ratios of juice combinations (2:1, 1:1, and 1:2). Observed parameters included cumulative pain inhibition, number of gastric ulcers, gastric pH, and organ indices of the stomach and liver. The results demonstrated that all treatment groups exhibited analgesic activity, with cumulative inhibition values higher than the negative control (28.0±19.8%), namely 47.3±18.2%, 53.6±11.4%, and 45.0±13.7%, although still lower than the positive control (75.0±16.2%). In the gastroprotective assessment, treatment groups reduced gastric ulcer formation without significant changes in gastric pH and organ indices. Overall, the 1:1 ratio showed the most balanced profile, combining effective analgesic activity, gastroprotection, and safety, indicating its potential as a natural dual-function therapeutic agent.